THE EFFECT OF EDUCATIONAL SELF-MEDICATION FOR DYSMENORRHEA TREATMENT USING OVER THE COUNTER DRUGS - Betti Dwi Kartikasari; Yustina Emi Setyobudi (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2018)
Self-medication is an attempt to treat the disease felt by using the over-the-counter drug (OTC) which is based on knowledge about the safe and rational treatment. The implementation of the self-medication drug use tends to be misused. The ease in self-medication treatment in community shows the importance of education in the use of medications safely and rationally. Education is carried out appropriately with effective methods and media. This research used quasi-experimental design approach with one group pretest posttest design. The sample of this research was 34 female students from Frateran High School Malang selected using a purposive sampling. The data was analyzed using Paired T-Test. The results of comparison of self-medication treatment using OTC drugs before (pre) and after (post) education provided the significance value obtained 0.000 which is smaller than alpha 0.05. The null hypothesis (H0) can be rejected and concluded that there is a different score in the self-medication treatment using OTC drugs before (pre) and after (post) education. It can be concluded that the education can affect the improvement of knowledge of the students for effectiveness of lowering OTC drugs abuse.